La dona, metamorfosi de la modernitat - Fabre, Gladys; Amaral, Aracy; Cuir, Raphaël; Ducros, Françoise; Irigaray, Luce; Malet, Rosa Maria; Molderings, Herbert; Monod-Fontaine, Isabelle; Rose, Barbara; Wong, Rita; Muelhens-Molderings, Barbara (Barcelona : Fundacio Joan Miró, 2004)
Albin-Guillot, Laure ; do Amaral, Tarsila ; Arndt, Gertrud ; Arp, Jean ; Taeuber-Arp, Sophie ; Bing, Ilse ; Bourgeois, Louise ; Braque, Georges ; Breslauer, Marianne ; Cahun, Claude ; Cunningham, Imogen ; Duchamp, Marcel ; Export, Valie ; Giacometti, Alberto ; Gondouin, Emmanuel ; Henri, Florence ; Hepworth, Barbara ; Jacobi, Lotte ; Kahlo, Frida ; Klein, Yves ; Krull, Germaine ; Kusama, Yayoi ; Lachaise, Gaston ; Lam, Wifredo ; Landau, Ergy ; Laurens, Henri ; Le Corbusier ; Léger, Fernand ; Man Ray ; Martins, Maria ; Masson, André ; Matisse, Henri ; Miró, Joan ; Moholy, Lucia ; Moore, Henry ; Moorman, Charlotte ; Paik, Nam June ; Yoko Ono ; Orlan ; Ozenfant, Amedée ; Picasso, Pablo ; de Saint Phalle, Niki ; Sanyu ; Schneemann, Carolee ; Soupault, Ré ; Zadkine, Ossip
boek